Actualization of the myth plot in the literary discourse (Eurasian Journal of Philology Science and Education, 2018)
The article deals with topical issues of the content and functioning of the mythological plot in anartistic text. The author proposes an original interpretation of the mythological plot, its narrative specificity in the space of a literary work. It is determined that the mythological plot is marked by a system ofmythological images and motifs, events, as well as in a special way structured by time and space. Thenamed myth markers act as the main «driving plot units» of the mythological plot in the artistic text. Themain and peripheral (additional) myth-subject lines are distinguished. The definition of myth-labeled textis introduced. The principles of construction of the mythological plot, the content of isomorphism withreference to the mythological text are investigated. The article is written within the framework of thegrant AP05133019 «Cultural codes of modern Kazakhstan (literary and media discourses)» funded by theCommittee of Science of the Ministry of Education and Science of the Republic of Kazakhstan.